The trip to Spain [videorecording (DVD)] - Winterbottom, Michael; Coogan, Steve; Brydon, Rob, 1965-; Keelan, Claire (Shout! Factory, 2017)
Two friends travel to different towns in Spain together, enjoying the different types of cuisine that each has to offer.